2020
DOI: 10.3892/ijo.2020.5138
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide antibiotics enhance the antitumor effect of lansoprazole resulting in lysosomal membrane permeabilization‑associated cell death

Abstract: The proton pump inhibitor lansoprazole (LPZ) inhibits the growth of several cancer cell lines, including A549 and CAL 27. We previously reported that macrolide antibiotics such as azithromycin (AZM) and clarithromycin (CAM) potently inhibit autophagic flux and that combining AZM or CAM with the epidermal growth factor receptor inhibitors enhanced their antitumor effect against various cancer cells. In the present study, we conducted the combination treatment with LPZ and macrolide antibiotics against A549 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Recently, we also showed that AZM enhanced the anti–cancer effect of lansoprazole (LPZ), a proton pump inhibitor, by upregulating LMP, although AZM or LPZ alone did not induce LMP in A549 cells. 35 Taken together, these results suggest that AZM induces lysosomal membrane fragility in cancer cells. Furthermore, it has been reported that malignant transformation alters lysosomal structure and functions and makes cancer cells more sensitive to lysosome‐targeting reagents, 36 , 37 suggesting that AZM could be a good candidate for cancer therapy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recently, we also showed that AZM enhanced the anti–cancer effect of lansoprazole (LPZ), a proton pump inhibitor, by upregulating LMP, although AZM or LPZ alone did not induce LMP in A549 cells. 35 Taken together, these results suggest that AZM induces lysosomal membrane fragility in cancer cells. Furthermore, it has been reported that malignant transformation alters lysosomal structure and functions and makes cancer cells more sensitive to lysosome‐targeting reagents, 36 , 37 suggesting that AZM could be a good candidate for cancer therapy.…”
Section: Discussionmentioning
confidence: 77%
“…Further studies are required to clarify the molecular mechanisms that connect LMP and apoptosis. Recently, we also showed that AZM enhanced the anti–cancer effect of lansoprazole (LPZ), a proton pump inhibitor, by upregulating LMP, although AZM or LPZ alone did not induce LMP in A549 cells 35 . Taken together, these results suggest that AZM induces lysosomal membrane fragility in cancer cells.…”
Section: Discussionmentioning
confidence: 82%
“…2.0 (Intron Biotechnology, Inc.) according to the manufacturer's instructions. As a positive control for necroptosis induction, HT-29 cells (ATCC), a colorectal adenocarcinoma cell line, were authenticated using STR profiling, pre-treated with Z-VAD-fmk (20 µM) in DMEM for 30 min, followed by additional treatment with CHX (10 µg/ml) and human TNF-α (20 ng/ml) for 8 h, as described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded onto a 60-mm dish (1x10 6 cells/dish) and pre-cultured for 24 h. After treatment with BTZ and/or RCS for 48 h, adherent cells were harvested by trypsinization. The cells were spread on glass slides by centrifugation (1,000 x g for 5 min at room temperature, then stained with May-Grünwald-Giemsa (Muto Pure Chemicals Co., Ltd.), as previously described (17). Samples were examined by digital light microscopy using a BZ-X810 microscope (Keyence Corporation).…”
Section: Assessment Of Cellular Proliferation Inhibitionmentioning
confidence: 99%
“…The interactions of macrolides with lipids are outlined in section B. Interactions with Lipids. AZM-induced lysosomal dysfunction was shown to result in lysosomal biogenesis and accumulation in several cancer cell lines, and although alone it did not cause cell death, it potentiated the anticancer action of a proton-pump inhibitor causing cell necrosis (Takeda et al, 2020). AZM lysosomal accumulation has also been shown in fibroblasts isolated from patients with IPF, which has been suggested to be related to AZMinduced apoptosis (Krempaska et al, 2020).…”
Section: A Actions On Lysosomes Apoptosis and Autophagymentioning
confidence: 99%